An Evaluation of the Tax-Transfer Treatment of Married Couples in European Countries - Herwig Immervoll; Henrik Jacobsen Kleven; Claus Thustrup Kreiner; Nicolaij Verdelin (University of Copenhagen, Economic Policy Research Unit (EPRU), 2008)
This paper presents an evaluation of the tax-transfer treatment of married couples in 15 EU countries using the EUROMOD microsimulation model. First, we show that many tax-transfer schemes in Europe feature negative jointness defined as a situation where the tax rate on one person depends negatively on the earnings of the spouse. This stands in contrast to the previous literature on this question, which has focused on a specific form of positive jointness. The presence of negative jointness is driven by family-based and means-tested transfer programs combined with tax systems that usually feature very little jointness. Second, we consider the labor supply distortion on secondary earners relative to primary earners implied by the current tax-transfer systems, and study the welfare effects of small reforms that change the relative taxation of spouses. By adopting a small-reform methodology, it is possible to set out a simple analysis based on more realistic labor supply models than those considered in the existing literature. We present microsimulations showing that simple revenue-neutral reforms that lower the tax burden on secondary earners are associated with substantial welfare gains in most countries. Finally, we consider the tax-transfer implications of marriage and estimate the so-called marriage penalty. For most countries, we find large marriage penalties at the bottom of the distribution driven primarily by features of the transfer system.
Keywords: 330; Haushaltseinkommen; Einkommensverteilung; Geschlecht; Steuervergünstigung; Öffentliche Sozialleistungen; Simulation; EU-Staaten